Caracterização química de antocianinas do inhame-roxo (Dioscorea trifida) - Parente, Guilherme de Sandes (2023)
Yam is a tuber belonging to the genus Dioscorea (Dioscoreaceae). Among the different cultivated species,for example, D.alata, D rotundata, D.opposite and D.trifida. This latter specie showing a purple color, due to the presence of anthocyanins. Yam has many health benefits, however, brazilian government agencies have giving little importance to its culture, so there is a need to further study yam. This work aimed to investigate the chemical composition of the brazilian purple yam (D.trifida), focusing on its anthocyanins. The anthocyanins present in tuber yam-purple (D.trifida) were extracted by the solid phase extraction (SPE), using water acidified with HCl or methanol acidified TFA as eluent , with subsequent analysis by Ultra-performance Liquid Chromatography coupled to Mass spectrometry and diode array detector (UPLC-QDa). In the extraction using water/HCl, seven substances were detected, while in the extraction with methanol/TFA, nine were detected. Most of the anthocyanins found were glycolyzed and acylated peonidin with ferulic acid. It was observed that in the extraction performed via methanol acidified with TFA there was a greater presence of aglycones. Finally, due to the numerous biological activities of anthocyanins, more studies will be needed to prove the beneficial health effects of consuming purple yam.